2020
DOI: 10.1590/s1519-99402121272020
|View full text |Cite
|
Sign up to set email alerts
|

Intake, digestibility and recovery of grains from feces of steers fed different oilseeds

Abstract: Oilseed grains are used as a protein and energy source, increasing the energy density of the feed. The goal of the present study was to determine the nutritional profile of canola, crambe and soybean grains recovered from feces, and to evaluate the intake and digestibility of nutrients, rumen fermentation parameters of beef cattle receiving whole grains of oilseeds. Three steers, 350 ± 23.5 kg body weight were distributed in a not contemporary, 3 × 3 double Latin square, and fed oilseed grains. Inclusion of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Rennó et al (2015) observed a decrease in DMI with an increase in soybean supply, without reducing the ADG of finishing Nellore young bulls. The results were attributed to the fact that the use of soybean in the diets favored feed efficiency and digestibility (Oliveira et al, 2020). Wanderley et al (2021) also studied the inclusion of oilseeds (cotton, sunflower, and soybean) to obtain diets with 70 g/kg of lipids for lactating cows and observed that the inclusion of oilseeds reduced the digestibility of DM and organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Rennó et al (2015) observed a decrease in DMI with an increase in soybean supply, without reducing the ADG of finishing Nellore young bulls. The results were attributed to the fact that the use of soybean in the diets favored feed efficiency and digestibility (Oliveira et al, 2020). Wanderley et al (2021) also studied the inclusion of oilseeds (cotton, sunflower, and soybean) to obtain diets with 70 g/kg of lipids for lactating cows and observed that the inclusion of oilseeds reduced the digestibility of DM and organic matter.…”
Section: Discussionmentioning
confidence: 99%